Recording mobile DNA in the gut microbiota using an Escherichia coli CRISPR-Cas spacer acquisition platform - Christian Munck (Nature Portfolio, 2020)
Horizontal gene transfer (HGT) in complex bacterial communities has been mostly studied using metagenomic analyses. Here, the authors develop an E. coli CRISPR-Cas spacer acquisition platform that allows real-time recording of HGT events at nucleotide-resolution, identifying diverse DNA transfer events in human clinical fecal samples.